Suppression of crosstalk in row-column actuator array using regulation of ferroelectric polarization - Park, Jin Soo; Jung soo young; Kim, Dong Hun; Park, Jung Ho; Jang, Ho Won; Kim, Tae Geun; Baek, Seung-Hyub; Lee, Byung Chul (Elsevier BV, 2023)
This article presents a method for suppressing electrical crosstalk in a ferroelectric row-column (RC) actuator array. In high-density two-dimensional (2D) arrays, the RC addressing scheme has advantages over the conventional method of fully addressing the array, primarily due to its requirement for fewer interconnections to drive the elements. However, electrical crosstalk is an undesirable side effect that restricts the practical use of RC arrays for sensing and actuation. To mitigate this crosstalk between elements and allow activation of the target element, an addressing method using orthogonal biasing is investigated for the RC array. Due to the voltage-dependent polarization state of the ferroelectric film, each element exhibits bias-sensitive activity. Applying a coercive voltage bias to the electrically coupled elements via row electrodes to minimize the net polarization and piezoelectric activity reduces electrical crosstalk, leaving only acoustic crosstalk in the array. The method using coercive voltage bias reduces crosstalk between the elements by 6.25 dB compared to the conventional method. Furthermore, applying a negative bias of 7 V to the target element enhances its activity and increases its dynamic displacement by 33%, thus alleviating the crosstalk by 7.25 dB. The on-off switching characteristics of the biasing method are examined to investigate the feasibility of adopting such biasing in area scanning techniques for potential applications, such as ultrasonic imaging. By adjusting the magnitude of the DC bias, on-off switching operation is demonstrated at 5 kHz while achieving a 3 dB on-off ratio.